MECHANISMS OF FORMING CRITICAL THINKING IN HIGHER EDUCATION STUDENTS BASED ON PROBLEM-BASED LEARNING - Tokhtamysheva Maftuna Khursanovna (Modern American Journals, 2025)
The article discusses the role of problem-based learning in the development of critical thinking in students, its pedagogical mechanisms and conditions for effectiveness. Methods that encourage students to think independently, argue, and analyze different points of view by creating problem situations are analyzed. The article also reflects interactive methods, principles of communication and cooperation, motivational and reflexive approaches in the formation of critical thinking.
Keywords: communication, critical thinking, problem-based learning, pedagogical mechanisms, interactive methods, independent thinking.